Assessment of Radiation Exposure Awareness among Medical and Dental Interns: A Questionnaire-Based Cross-Sectional Study - Subhash Chandra Yadav; Sandip Gautam; Sanju Rawal (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Radiology is an integral part of modern medicine, but there are known potential risks of ionizing radiation that can lead to serious health hazards. Many studies indicate that primary care physicians are unaware of the risks associated with the use of radiation which is a growing concern. The objective of this study was to assess the knowledge of radiation awareness among medical and dental interns at UCMS-TH. MATERIAL AND METHODS A cross-sectional study was conducted among medical and dental interns at UCMS-TH, Bhairahawa, Nepal. One hundred eighteen participants were included in the study based on inclusion/exclusion criteria over a four-month period (from July to October 2018). Participants were surveyed by using the MCQ questionnaire and data were analyzed using SPSS software version 20. RESULTS A total of 118 interns (78 medical and 40 dental interns) participated in this study. The mean score of knowledge of medical interns was 6.95±3.04, range 1 to 13 out of 14. In a questionnaire survey, 52.6% had good knowledge and 47.4% had poor knowledge about radiation. The mean score of knowledge of dental interns was 8.03±2.58, range 1 to 13 out of 14. In a question- naire survey, 75% had good knowledge and 25% had poor knowledge about radiation. CONCLUSION The general knowledge of radiation awareness was good among medical and dental interns, but the radiation awareness of dental interns was higher than that of medical interns. It was recommended that courses/seminars/training courses on radiation protection for medical students to be held and conducted.